Determination and validation of acetazolamide tablets 250mg by UV double beam spectrophotometry - KK.Senthilkumar; S.vigneswaran; K.vidhyapriya; V.venkatesh; S.veeramanikandan (International Journal of Pharmacy and Analytical Research, 2022)
Analytical monitoring of a ph armaceutical product or of s pecific ingredients within the product is necessary to ensure its safety efficacy throughout all phases of its shelf life. Such monitoring is in accordance with the specifications elaborated during product develop ment. Analytical validation is t he corner stone of process validation without a proven measurement system it is impossible to confirm whether the manufacturing process has done what it purports to do. All new methods developed are validated . Determination of Acetazolamide in a fixed dosage form was carried out by UV Spectrophotometric method. The absorbance values were observed for different d ilutions of drug at 263.00 nm and which are used for the dilution in Ethanol. This method obeys Beer‟s Lambert‟s Law in the concentration range of 1 -5µg/ml. The results have been validated statistically and the recovery studies confirmed the accuracy of th is proposed method.